Immunopeptidome screening to design An immunogenic construct against PRAME positive breast cancer; An in silico study. (April 2020) - Afzali, Farzaneh; Minuchehr, Zarrin; Jahangiri, Samira; Ranjbar, Mohammad Mehdi
Graphical abstract: Highlights: Investigating and validation of PRAME co-expressed genes. Establishing protein-protein interaction network of PRAME and enrichment analysis. Design novel multi-epitope BC vaccine against PRAME. Prediction and modeling of secondary and tertiary structures of PRAME derived vaccine. In-silico validation of the designed construct by studying modelled tertiary structure, physiochemical characterization, safety, antigenicity, post-translational modification, solubility, and docking simulation. Abstract: Background: Metastasis is the main cause of breast cancer (BC) lethality, especially in early stages, led to improvements in therapeutic procedures. Lately, by improvements in our perception of biological processes and immune system new classes of vaccines are emerged that grant us the opportunity of designing resolute constructs against desired antigens. In the current study, we used a variety of immunoinformatics tools to design a novel cancer vaccine against Preferentially Expressed Antigen of Melanoma (PRAME), which counts as a cancer testis antigen for various human cancers including BC. The PRAME up-regulation leads to strengthen BC stem cells maintenance, drug resistance, cell survival, adaptation, and apoptosis evading in cancerous cells. Methods and results: The PRAME co-expressed genes were mined and validated through BC RNA-sequencing of TCGA data. The immunodominant T-cell predicted epitopes were fused and engineered to form the vaccine. The safety, allergenicity, and immunogenic capabilities of the vaccine were confirmed by promising immunoinformatics tools. The vaccine's structure was verified to be hydrophilic in most areas through Kyte and Doolittle hydrophobicity plotting. The interactions between the designed vaccine and immune receptors of TLR4 and IL1R were confirmed by protein-protein docking after modeling its tertiary structure. Finally, codon optimization and in silico cloning were performed to guarantee better in-vivo results. Conclusion: In conclusion, concerning in silico assessments' results in this study, the designed vaccine can potentially boost immune responses against PRAME, therefore may decrease BC development and metastasis. According to the mined PRAME co-expressed genes and their functional annotation, cell cycle regulation is the prime mechanism opted by this construct and its adjacent regulatory genes along boosting immune reactions.